CRC standard mathematical tables and formulae - Zwillinger, Daniel, 1957- (CRC Press, 2012)
With over 6,000 entries, CRC Standard Mathematical Tables and Formulae, 32nd Edition continues to provide essential formulas, tables, figures, and descriptions, including many diagrams, group tables, and integrals not available online. This new edition incorporates important topics that are unfamiliar to some readers, such as visual proofs and sequences, and illustrates how mathematical information is interpreted. Material is presented in a multisectional format, with each section containing a valuable collection of fundamental tabular and expository reference material. New to the 32nd EditionA.
Keywords: Mathematics -- Tables.; Mathematics.; elektronické knihy; electronic books